PENGARUH ALOKASI DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KOKOWAHOR KECAMATAN KANGAE KABUPATEN SIKKA - Cindi Claudia; Maria Indriyani H. Tiwu; Aldarine Molidya3 (Bajang Institute, 2026)
This study aims to determine the influence of village fund allocation on community welfare in Kokowahor Village, Kangae District, Sikka Regency. The research employed a qualitative method with data collection techniques through interviews, observation, and documentation. The research informants consisted of the Acting Village Head, Village Secretary, Village Treasurer, Head of the Village Consultative Body (BPD), and the community. The findings indicate that the allocation of village funds has a positive impact on community welfare. Assistance programs such as the construction of pig pens, provision of piglets, and the development of sanitation facilities (latrines) were considered successful and provided tangible benefits. The community felt supported in improving their living standards, enhancing sanitation conditions, and gaining economic support from the livestock sector. Based on these findings, it can be concluded that the management of village fund allocation in Kokowahor Village has significantly contributed to improving community welfare through development and empowerment programs.